How does arm motion enhance vertical jump performance- a simulation study - Chen, H. C.; Chen, H. C.; Cheng, K. B. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The mechanisms enabling the arms to increase standing vertical jump height are investigated by computer simulation. The human models actuated by joint torque generators consist of four/five segments connected by frictionless joints. Simulation initiates from a balanced static posture and ends at jump takeoff. Joint activation timings are optimized to produce maximum Jump height. Jumping performance is enhanced by arm motion in increased mass centre height and takeoff vertical velocity, which contributes about 1/3 and 2/3 to the increased height, respectively. Arm swing also elongates the durations of hip torque generation and ground contact period. Theories explaining the performance enhancement caused by arms are examined. Because shoulder joint force due to arm motion does not precisely reflect in the changes of vertical ground reaction force, the force transmission theory is doubtful. The joint torque/work augmentation theory is accepted at the hip but not knee and ankle because only the hip joint work is considerably increased. Since shoulder joint work is responsible for around half of the additional energy created by arm motion, the pull/impart energy theory is also granted.